Eliminating Noise of Mud Pressure Phase Shift Keying Signals with A Self-Adaptive Filter - Yue Shen; Lingtan Zhang; Heng Zhang; Yinao Su; Limin Sheng; Lin Li (Institute of Advanced Engineering and Science, 2013)
The feasibility of applying a self-adaptive filter to eliminate noise in the downhole mud pressure phase shift keying (PSK) signals is studied. The self-adaptive filter with carrier wave as the filter input signal and mud pressure PSK signal including noise as the filter expected input signal in structure was adopted to process the mud pressure PSK signals with the broadband signal characteristic in communication. Mathematical model of the filter was built to reconstruct the mud pressure PSK signals based on the evaluation criterion of least mean square error (LMS) and the mathematical model of mud pressure PSK signals. According to the filter mathematical model, a special self-adaptive control algorithm was adopted to realize the filter by adjusting the filter weight coefficients self-adaptively and the impacts of the filter step-size factor on signal to noise ratio (SNR) and distortion factors of the reconstructed mud pressure PSK signals were analyzed. Numerical calculation and simulation show that the self-adaptive filter can efficiently eliminate random noise in the signal frequency band and reconstruct the mud pressure PSK signals. In addition, low distortion factors of the reconstructed mud pressure PSK signals can be obtained by reasonable selecting the filter step-size factor. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2610